CLAUSE STRUCTURE TYPOLOGY OF INDONESIAN TRANSITIVE VERB WITH SUFFIX -KAN - Putu Devi Maharani; IGB Wahyu Nugraha Putra (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This study uses a linguistic typology approach in finding the peculiarities of the use of suffix -kan in Indonesian verbs. The data of this research were taken from a novel entitled Larung which was written by an Indonesian novelist. Some representative data are analyzed in this article to show the syntactic structure of transitive verb clauses with the suffix -kan in Indonesian, how the typology of language is reflected in the clauses of transitive verbs with the suffix -kan and how the variations in meaning are produced. The results of this study found that there were four types of syntactic structures found in clauses with transitive verbs with the suffix -kan in the novel, namely NP VP NP, NP VP NP NP, NP VP PP, and NP VP PP PP. Typologically, there are two variations of agents that appear as a result of transitive verbs with the suffix -kan in clauses in this novel, namely A-O/P and A-O-E. Semantically, the meaning of transitive verbs with the suffix -kan in the clauses and sentences contained in this novel is as causative, beneficial and inherently-optional. Keywords— Typology, Indonesian Transitive Verb, Suffix -kan